Cytokine response after radical operations for tumors of the colon - Zavgorodniy, Alexander (ScienceRise: Medical Science, 2017)
In cancer patients, who underwent wide planned surgical operations as to a tumor of the colon, in postoperative period immune suppression may be caused by an inflammatory reaction that directly influences the number of postoperative complications. Aim of research – the comparative assessment of the influence of postoperative anesthesia methods on the cytokine response of an organism. Materials and methods. There were examined 102 patients with tumors of the colon. All patients after operations were hospitalized at the department of intensive care. The control group (N=53) was anesthetized by non-steroid anti-inflammatory preparations together with opiates. The studied group (N=49) received the continuous prolonged epidural analgesia within multimodal anesthesia. There were studied the pain level (by 10-point visually analogous scale), influence on the change of anti-inflammatory and inflammatory cytokines on the cytokine response. The levels of IL-1β, IL-4, IL-10 and TNF were studied. Results. The study of cytokines level demonstrated that at 3 day after the operation in the studied group of patients (continuous prolonged epidural analgesia) the level of anti-inflammatory cytokines decreased and the level of inflammatory ones increased. It allows to note the positive influence of the continuous prolonged epidural analgesia on the cytokine response in the organism of patients, operated as to colon tumors. Conclusions. The prolonged continuous epidural analgesia within multimodal anesthesia provides the adequate postoperative analgesia after operations as to colon tumors. In favors the stable anesthesia and excludes periodical exacerbations of pain syndrome. It stimulates anti-inflammatory cytokines production, decreases the cytokine response of the organism to the operative trauma after the surgical treatment of colon tumors